2005
DOI: 10.1007/s11010-005-7500-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of follicle-stimulating hormone and vitamin A upon purinergic secretion by rat Sertoli cells

Abstract: Follicle-stimulating hormone (FSH) and vitamin A (retinol) are two of the main regulators of the male reproductive system. Recently, it has been described that extracellular purines can affect some important reproductive-related functions in Sertoli cells and germinative cells, by activating specific purinergic receptors. In this work, we report that both FSH and retinol are able to induce changes in the levels of extracellular purines of cultured rat Sertoli cells. FSH induced an increase in adenosine, mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Intriguingly, the P2X7 receptor has also been shown to function as an ATP-induced ATP release route (Pellegatti et al, 2005;Suadicani et al, 2006). Although FSH-dependent ATP release from Sertoli cells has been shown (Gelain et al, 2003(Gelain et al, , 2005 and ATP secretion from germ cells has been postulated (Lalevée et al, 1999), a potential self-enhancement mechanism via P2X7 receptors within the seminiferous epithelium has never been addressed. Therefore, we performed quantitative LC-MS/MS analysis of [ATP] ex in seminiferous tissue samples (Fig.…”
Section: P2x7 Receptors Mediate Low-affinity Atp Responses In Spermatmentioning
confidence: 99%
See 2 more Smart Citations
“…Intriguingly, the P2X7 receptor has also been shown to function as an ATP-induced ATP release route (Pellegatti et al, 2005;Suadicani et al, 2006). Although FSH-dependent ATP release from Sertoli cells has been shown (Gelain et al, 2003(Gelain et al, , 2005 and ATP secretion from germ cells has been postulated (Lalevée et al, 1999), a potential self-enhancement mechanism via P2X7 receptors within the seminiferous epithelium has never been addressed. Therefore, we performed quantitative LC-MS/MS analysis of [ATP] ex in seminiferous tissue samples (Fig.…”
Section: P2x7 Receptors Mediate Low-affinity Atp Responses In Spermatmentioning
confidence: 99%
“…Recently, we and others suggested that purinergic signaling constitutes a critical component of testicular auto/paracrine communication (Filippini et al, 1994;Foresta et al, 1995;Gelain et al, 2003;Ko et al, 2003;Poletto Chaves et al, 2006;Antonio et al, 2009;Veitinger et al, 2011). In Sertoli cells, P2X2-and P2Y2dependent Ca 2+ signals counteract various effects mediated by follicle-stimulating hormone (FSH) and alter estradiol production, enzyme activity, and secretory behavior (Rudge et al, 1995;Meroni et al, 1998;Rossato et al, 2001;Gelain et al, 2005;Veitinger et al, 2011). Moreover, ATP secretion from Sertoli cells is itself under endocrine control (Lalevée et al, 1999;Gelain et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soybean is an endocrine disruptor in males [11] and it is rather probable that soybean may have disrupted the synergy between testosterone and follicle stimulating hormone during the process of spermatogenesis [6,11,21]. Ikpeme et al [21] assertively revealed that the distortion in fertility in male mammals is directly correlated with the disruption of spermatogenesis and the hormone regulatory machineries.…”
Section: Discussionmentioning
confidence: 99%
“…According to Hess [4] and Glover and Assinder [5], distortions in the fertility of male mammals is directly correlated to the distortions in spermatogenesis. Reduction in spermatogenic activities has also been reported to result in infertility, reproductive toxicity and dysfunctions [6].…”
Section: Introductionmentioning
confidence: 99%